P2P in the Networked Future of European Cinema. - CARDOSO, GUSTAVO; CAETANO, MIGUEL; ESPANHA, RITA; JACOBETTY, PEDRO; QUINTANILHA, TIAGO LIMA (International Journal of Communication (19328036), 2012)
The new peer-to-peer (P2P) technologies have impacted the film industry, which advocates sanctions against the downloading and sharing of products found on the Internet. But the economic effect of file sharing on the film industry remains difficult to determine. In this article, we ask whether file sharing networks will affect the survival or potential growth of European cinema. The steady decline in traditional film distribution channels for European productions-cinema theatres and direct sales or renting-is leading to the emergence of new distribution channels. And yet the results of the movie industry's calls-including those voiced by its European players-for stronger legislation against these same distribution channels are making their way through Europe by means of enforcement tools like HADOPI and other graduated response programs. Our hypothesis is that this offensive runs the risk of condemning a potential open distribution network and commons business model at its birth. For this, we start by clarifying the emerging global P2P phenomenon; we then stipulate what we mean by European cinema, outline its peculiar traits, and contrast it with North American cinema. Finally, we compare the consumption of European film in theatres with the availability of seeds and leechers for European cinema in P2P networks.